L'influence de Husserl en Russie au début du XXème siècle et son impact sur les émigrés russes de Prague - Dennes, Maryse (Cahiers du Centre de Linguistique et des Sciences du Langage, 2022)
Maryse DENNES (University of Bordeaux III) : «Husserl's influence in Russia in the Beginning of the XXth Century and on the Russian Emigrés in Prague» In Russia, in the beginning of the twentieth century, Husserl’s work influenced some Russian philosophers who would later be in Prague (N. Losskij, B. Jakovenko). At Moscow university, R. Jakobson studied the «Logical researches» at first, then he met G. Špet, the leader of the Russian phenomenologic school. Špet's contribution to the activities of the Moscow Linguistic Circle was of main importance for Russian linguists who would later participate to the Prague Linguistic Circle (R. Jakobson, P. Bogatyrev). Considering the influence of phenomenology in Russia, we can also mention the importance of Baxtin's and Tynjanov's thoughts for the work of the Prague Linguist Circle.